Advances in human factors, business management, training and education : proceedings of the AHFE 2016 International Conference on Human Factors, Business Management and Society, July 27-31, 2016, Walt Disney World®, Florida, USA - Kantola, Jussi; Barath, Tibor, 1956-; Nazir, Salman; Andre, Terence S., 1964- (Advances in intelligent systems and computing ;, 2016)
This book reports on practical approaches for facilitating the process of achieving excellence in the management and leadership of organizational resources. It shows how the principles of creating shared value can be applied to ensure faster learning, training, business development, and social renewal. In particular, the book presents novel methods and tools for tackling the complexity of management and learning in both business organizations and society. It covers ontologies, intelligent management systems, methods for creating knowledge and value added. It gives novel insights into time management and operations optimization, as well as advanced methods for evaluating customers' satisfaction and conscious experience. Based on the AHFE 2016 International Conference on Human Factors, Business Management and Society, held on July 27-31, 2016, Walt Disney World®, Florida, USA, the book provides both researchers and professionals with new tools and inspiring ideas for achieving excellence in various business activities.